2021
DOI: 10.1080/19420889.2021.1965718
|View full text |Cite
|
Sign up to set email alerts
|

Infrared light therapy relieves TLR-4 dependent hyper-inflammation of the type induced by COVID-19

Abstract: The leading cause of mortality from COVID-19 infection is respiratory distress due to an exaggerated host immune response, resulting in hyper-inflammation and ensuing cytokine storms in the lungs. Current drug-based therapies are of limited efficacy, costly, and have potential negative side effects. By contrast, photobiomodulation therapy, which involves periodic brief exposure to red or infrared light, is a noninvasive, safe, and affordable method that is currently being used to treat a wide range of diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Our results are also consistent with in vitro studies on human cell lines investigating the anti-inflammatory effects of PBM. Aguida et al found that daily exposure of HEK293 cells to two 10-min, high-intensity periods of IR light caused a significant reduction in the TLR-4 dependent inflammatory response pathway ( Aguida et al, 2021 ). In particular, within 2 days of treatment, they found that exposure to the light source resulted in a significant decline in NF-κB and AP1 activity, and decreased expression of IL-6, IL-8, TNF-α, IFN-α, and IFN-β.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with in vitro studies on human cell lines investigating the anti-inflammatory effects of PBM. Aguida et al found that daily exposure of HEK293 cells to two 10-min, high-intensity periods of IR light caused a significant reduction in the TLR-4 dependent inflammatory response pathway ( Aguida et al, 2021 ). In particular, within 2 days of treatment, they found that exposure to the light source resulted in a significant decline in NF-κB and AP1 activity, and decreased expression of IL-6, IL-8, TNF-α, IFN-α, and IFN-β.…”
Section: Discussionmentioning
confidence: 99%
“…The authors "further discussed technical considerations involving light sources and exposure conditions to put their observations into potential clinical use to treat COVID-19" [51].…”
Section: Experimental Models Give Insight Into Future Applications Of...mentioning
confidence: 99%
“…It can promote healthy sleep, guard against oxidative stress, and lessen inflammation and pain. Infrared's inflammation-reducing properties have led to its use in several treatment regimens, including the treatment of COVID-19 [7]. Red light, in this case, provides a non-invasive and affordable method to treat various inflammatory conditions.…”
Section: Low-level Light Therapy In Burns Treatmentmentioning
confidence: 99%